2019
DOI: 10.1002/ejoc.201801621
|View full text |Cite
|
Sign up to set email alerts
|

Fluorene Derivatives Bearing Halogenomethyl Groups: Synthesis, Molecular Structures, and Halogen/Hydrogen Bonding Patterns in the Crystalline State

Abstract: 9,9‐Diethylfluorenes bearing chloromethyl, bromomethyl, and iodomethyl groups in the 2, 4, and 7 positions of the aromatic skeleton were prepared and their solid‐state structures determined by single‐crystal X‐ray diffraction analysis. The prepared fluorenes represent not only valuable starting materials for a wide range of fluorene‐based compounds but are also interesting objects for the analysis of the supramolecular motifs in the crystalline state. The X‐ray diffraction experiments revealed that the asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 94 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…Recently we have reported the syntheses of compounds 1 and 2 on the basis of a three-step procedure, [9] starting with the ethylation of 9H-fluorene (see Scheme 1 and Scheme S1). The 9,9-diethyl-9H-fluorene (9) was further converted into 2,7-bis (bromomethyl)-9,9-diethyl-9H-fluorene (7) and 2,4,7-tris (bromomethyl)-9,9-diethyl-9H-fluorene (8), which were finally treated with potassium phthalimide to obtain the desired compounds 1 and 2. We have now found that the incorporation Figure 1.…”
Section: Synthesis Of Compounds 1-6 and Their Conversion To Derivatives Bearing Primary Amino Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we have reported the syntheses of compounds 1 and 2 on the basis of a three-step procedure, [9] starting with the ethylation of 9H-fluorene (see Scheme 1 and Scheme S1). The 9,9-diethyl-9H-fluorene (9) was further converted into 2,7-bis (bromomethyl)-9,9-diethyl-9H-fluorene (7) and 2,4,7-tris (bromomethyl)-9,9-diethyl-9H-fluorene (8), which were finally treated with potassium phthalimide to obtain the desired compounds 1 and 2. We have now found that the incorporation Figure 1.…”
Section: Synthesis Of Compounds 1-6 and Their Conversion To Derivatives Bearing Primary Amino Groupsmentioning
confidence: 99%
“…Fluorenes bearing halogen, formyl, or amino groups are useful starting materials for a wide range of fluorene-based acyclic and macrocyclic compounds as well as polymers. Recently, we have described the syntheses and crystal structures of halogenomethyl substituted 9,9-diethylfluorenes [8] as well as their further synthetic transformations. [8,9] For example, 2,4,7-tris(bromomethyl)-9,9diethyl-9H-fluorene was the basis for the syntheses of a series of 9,9-diethyl-9H-fluorenes bearing various functional groups, [9] some of which are shown in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we have described the syntheses and crystal structures of halogenomethyl-substituted 9,9-diethylfluorenes 1-3 ( Figure 1), which are not only valuable starting materials for the preparation of various fluorene-based compounds, but also interesting building blocks for the formation of different supramolecular motifs in the crystalline state. [9] For example, the crystal structure of the iodomethyl substituted derivative 3 is characterized by the presence of an unusual triangular I 3 synthon consisting of two I•••I contacts with type I geometry and one I•••I contact that corresponds to the polarization-induced type II category. Regarding the synthetic applications described in our previous work, [9] the efficient one-step synthesis of 9,9-diethylfluorene-2,4,7-tricarbaldehyde (4) on the basis of 2,4,7-tris(bromomethyl)-9,9-diethylfluorene (2), providing three-fold higher yield of 4 than the known three-step reaction sequence, is worthy of particular mention.…”
Section: Introductionmentioning
confidence: 99%
“…[9] For example, the crystal structure of the iodomethyl substituted derivative 3 is characterized by the presence of an unusual triangular I 3 synthon consisting of two I•••I contacts with type I geometry and one I•••I contact that corresponds to the polarization-induced type II category. Regarding the synthetic applications described in our previous work, [9] the efficient one-step synthesis of 9,9-diethylfluorene-2,4,7-tricarbaldehyde (4) on the basis of 2,4,7-tris(bromomethyl)-9,9-diethylfluorene (2), providing three-fold higher yield of 4 than the known three-step reaction sequence, is worthy of particular mention.…”
Section: Introductionmentioning
confidence: 99%